2014
DOI: 10.1021/cm502953s
|View full text |Cite
|
Sign up to set email alerts
|

Germanosilicate Precursors of ADORable Zeolites Obtained by Disassembly of ITH, ITR, and IWR Zeolites

Abstract: Structure transformation of germanosilicate zeolites ITH, ITR, and IWR containing hydrolytically unstable interlayer Ge–O bonds was investigated and is related to the conditions of acidic treatment (i.e., concentration of hydrochloric acid, temperature, duration). The disassembly of ITH (Si/Ge = 2.5), ITR (Si/Ge = 2.4), and IWR (Si/Ge = 6.9) zeolites under appropriate acidic treatment was demonstrated. Low-concentration acid solutions (e.g., 0.01 M HCl) and low temperatures favor the hydrolysis of the zeolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 66 publications
(101 citation statements)
references
References 45 publications
4
94
0
3
Order By: Relevance
“…Indeed, a number of MOFs and zeolites, unattainable through traditional techniques, have already been prepared by innovative methods such as transmetallation, solvent‐assisted linker exchange (SALE), assembly‐disassembly‐organization‐reassembly (ADOR), ball milling and other means . The ADOR method uses weaknesses in structures, created selectively by replacing silicon by other elements [boron (B) or germanium (Ge)], to synthesize new zeolites . The core idea is: first, to replace silicon with B or Ge, and then selectively remove heteroatoms from zeolites using acid hydrolysis.…”
Section: Figuresupporting
confidence: 62%
“…Indeed, a number of MOFs and zeolites, unattainable through traditional techniques, have already been prepared by innovative methods such as transmetallation, solvent‐assisted linker exchange (SALE), assembly‐disassembly‐organization‐reassembly (ADOR), ball milling and other means . The ADOR method uses weaknesses in structures, created selectively by replacing silicon by other elements [boron (B) or germanium (Ge)], to synthesize new zeolites . The core idea is: first, to replace silicon with B or Ge, and then selectively remove heteroatoms from zeolites using acid hydrolysis.…”
Section: Figuresupporting
confidence: 62%
“…But it is not always the case. [ 110 ] It was found that low concentration acid solution and low temperatures favored the hydrolysis process, and the effi ciency was strongly related with the chemical composition of the parent zeolites. In some cases, Ge-rich D 4 R units distribute only along one direction and act as pillars supporting the silica layers, such as in germanosilicates with UTL, [ 101,105 ] ITH, [ 106 ] IWW [ 107 ] topologies.…”
Section: Top-down Methods To 2d Zeolites and Ador Process To Novel Zeomentioning
confidence: 99%
“…4C). The formation of extra-porosity not observing during the alumination of Ge-poor ITH-6 zeolite treatment with Al(NO 3 ) 3 solution is likely caused by "unsuitable" distribution of extractable Ge atoms in the framework (the absence of [4Si;4Ge] 25 domains according to the NMR data 23 ). (Fig.…”
Section: Ith-n/al/80 (Blue) and Ith-n/al/175 (Red)mentioning
confidence: 99%
“…Since the conditions of the treatment (pH = 2.0, T = 80 or 175 °C) are sufficient for extraction of the most Ge from the framework ( Table 2), it is 5 reasonable to assume that the first stage of overall process is the breaking of Si-O-Ge bonds in D4Rs. 23 This leads to the formation of silanol defects in all ITH zeolites under investigation (Fig. 5A) as well as to the creation of ultramicroand mesopores in ITH-1 or ITH-2 zeolites (Fig.…”
mentioning
confidence: 99%